Human Relationships with Grave Trees in Eastern Slavic and Polish Verbal Folklore (Selected Examples). The Perspective of a More-Than-Human Anthropology - Filipowicz, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2024)
The motif of the relationship between people and trees, often present in Eastern Slavic folk literature, although discussed many times, still seems to offer undiminished interpretive potential. In the light of contemporary – postcolonial and postsecular – social anthropology, it can be read as a representation of belief practices that implement assumptions close to indigenous approaches to natural reality. This is indicated in particular by the non-anthropocentric attitude to the tree, usually understood as a personal entity, demonstrating an ability to transform the world analogous to humans, and also having the ability to extend human life in a material, not just symbolic, way. This applies especially to trees growing or planted on graves, widespread in North Russian and Belarusian tradition, and artifacts made from their wood, such as musical instruments. They demonstrate a “resurrection potential” towards the dead, which corresponds to the understanding of continuity between humans and non-humans, characteristic of animistic indigenous cultures, as well as between existence during life and after death.